Teori Hukum Acara Peradilan Konstitusi - Reynold Simanjuntak; Frederico Louis Fan Gonggonang (CV. ITTC INDONESIA, 2024)
This study aims to analyze the theory of procedural law in constitutional court trials in Indonesia. Specifically, it investigates the effectiveness and challenges of implementing procedural law in the Constitutional Court (Mahkamah Konstitusi), and explores the potential for reforms to improve transparency, accessibility, and fairness in the process. The study employs a qualitative research approach using a literature review method. Various sources such as legal books, journal articles, legal documents, and research reports are reviewed to understand the current procedural law theory. No experimental tools or surveys were used, but secondary data from credible sources like Google Scholar and JSTOR were analyzed. Microsoft Word was used for writing, while Zotero was employed for reference management. The study finds that although the procedural law in constitutional trials is theoretically clear, its implementation faces significant challenges. These challenges include complex and technical procedures that hinder public access to justice, limited transparency in decision-making, and inconsistent application of legal rules. The research suggests that simplifying and improving the clarity of procedural laws could enhance fairness and public trust in the Constitutional Court. This study is limited by its reliance on secondary data and does not include primary data collection through surveys or interviews. Additionally, it focuses only on the Indonesian Constitutional Court, and the findings may not be applicable to other jurisdictions. This research contributes to the field of constitutional law by providing recommendations for improving procedural law in Indonesia's Constitutional Court. It can benefit legal scholars, practitioners, and policymakers who seek to enhance the effectiveness and transparency of constitutional trials.